BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
The Illustrated Dictionary of Plant Pathology Author: DR. N.L. VYAS, CAZRI, RRS, Bikaner, Scientific Publishers, Jodhpur, 1995. Integrated Diseases Management and Plant Health. Editors, V.K. Gupta and R.C. Sharma, Scientific Publishers, Jodhpur, 1995, 319 pp; ISBN: 81-7233-106-5.